The future of security in a remote-work environment. Issue 10 (October 2021) - Sabin, Jason
Abstract : Cyber security threats were a concern before the Covid-19 pandemic. But a year after businesses and employees vacated office complexes, the risks of falling victim to a cyber attack have only grown. In an article published by the Journal of Medical Internet Research, researchers found that the number of cyber attacks increased by 500% throughout the pandemic, and by 2021 are on track to cost world businesses $6tr annually. 1